A Study of Error Analysis from Students’ Sentences in Writing - Rizki Ananda; Sofyan A. Gani; Rosnani Sahardin (Universitas Syiah Kuala, 2014)
This study was to investigate the types of sentence errors and their frequency made by first grade students from a high school in Banda Aceh in their writing of English. The participants for this study were 44 first graders chosen by random sampling. The research method used was quantitative as the data was analyzed with a statistical procedure. The data was obtained from written tests for a descriptive text entitled “My school” of 120-140 word length. This study found that three out of four sentence errors in the students’ writing were fragmented sentences whilst nearly a quarter of the errors were run-on or comma splice sentences. There were only a few choppy sentence errors and no stringy sentence errors. The data revealed five types of fragmented sentences: these were the absence of a subject, the absence of a verb, the absence of both a subject and a verb, the absence of a verb in a dependent clause, and the absence of an independent clause.